Prospective study of hypothalamo-hypophyseal dysfunction in children and adolescents following traumatic brain injury - Krahulik, David; Aleksijevic, Darina; Smolka, Vratislav; Klaskova, Eva; Venhacova, Petra; Vaverka, Miroslav; Mihal, Vladimir; Zapletalova, Jirina (Biomedical papers, 2017)
Background and Aims: Retrospective studies of TBI have found a neuroendocrine dysfunction following traumatic brain injury in 23 to 60% of adults and 15 to 21% of children. Our aims were to determine the prevalence of hypothalamo-hypophyseal dysfunction in children following brain injury, assess its relationship to the type of injury and the course of the acute post-traumatic phase. Patients and Methods: Body development (growth, pubertal development, and skeletal maturity) were evaluated in 58 patients (21 girls) after a brain injury rated 3 to 12 on the Glasgow Coma Scale (GCS). The patients underwent standard endocrine tests - TSH, fT4, IGF-1, PRL, morning cortisol, FSH, LH, and testosterone in boys and estradiol in girls - in the early post-traumatic period (2 to 14 days; T0) and at 3, 6, and 12 months after the injury (T3, T6, and T12). Dynamic tests were carried out in patients with abnormalities in their clinical examination and/or laboratory results. An MRI was performed on all patients at T12. Results: The median age at the time of injury was 11.3 (0.5 to 18.7) years. Of the 58 patients, 23 had GCS < 8, corresponding to severe brain injury. At T0, diabetes insipidus (DI) was diagnosed in 12 patients, and the syndrome of inappropriate antidiuretic hormone secretion (SIADH) was found in 4 patients. Frequent hormonal changes simulated central hypothyroidism (in 45% of patients) and hypogonadotropic hypogonadism (in 25% of adolescents who were already pubertal at the time of injury > Tanner II). Examination at T3 (n = 58) confirmed a combined pituitary hormone deficiency in two boys and DI in another one. At T6 (n = 49), hormonal dysfunctions were diagnosed in two boys (precocious puberty and growth hormone deficiency). At T12 (n = 39), a new endocrine dysfunction was diagnosed in five patients (growth hormone deficiency in two, hypogonadotropic hypogonadism in two, and in one patient, already diagnosed with a growth hormone deficiency, central hypothyroidism, as well). Brain MRI revealed an empty sella in two patients with growth hormone deficiency. Patients with GCS < 8 had more symptoms of SIADH or DI in the early post-traumatic period 11/23 vs. patients with GCS of 8 to 13 (4/35), and more frequent hormonal disorder (6/23) than individuals with moderate trauma (3/35), P = 0.0135. The incidence of endocrine dysfunction at T0 significantly correlated with the severity of injury (P = 0.05), but it was not an indicator for the development of a late hormonal disorder. Conclusion: Within a year after injury, a hormonal disorder was found in 17.6% of the patients. Neuroendocrine dysfunction as a late consequence of craniocerebral trauma in children and adolescents was less frequent than in adults. Risk factors for its development are the gravity of the injury, brain scan pathology, and possibly the development of DI, SIADH, or CSWS in the acute post-traumatic phase.
Keywords: traumatic brain injury; children; post-traumatic hormonal disorder; growth hormone deficiency; precocious puberty; risk factors